Integration of Fourier and Wavelet Transform for Adsorption Mechanism of Cesium Study Based on X-Ray Diffraction and Absorption Spectroscopy - Chi-Wen Hsieh; Zih-Shiuan Chiou; Chuan-Pin Lee; Shih-Chin Tsai; Wei-Hsiang Tseng; Yu-Hung Wang; Hui-Min Chiu; Qi-Rui Sun; Chun-Liang Yeh (IEEE Access)
The safety and storage of nuclear disposal plays a critical challenge in the utilization of radiology applications such as for nuclear medicine, radiotherapy, nuclear energy, particularly concerning the environmental behavior of radio-materials. One of the most concerning materials is radiocalcium due to its physical and chemical mechanism and half-life period. In this study, several minerals were collected, including basalt, argillite, mudrock and granite for the batch tests. In analysis stage, X-ray diffraction and absorption spectroscopy were used for radio-Cs LIII-edge adsorption study. The batch test process shows that basalt, argillite, and mudrock exhibited strong adsorption effectiveness for Cs, with distribution coefficient values ( $\ge 700$ mL/g). In contrast, granite from two different locations showed lower distribution coefficient values (<15 mL/g) after adsorption, with pH also affecting the adsorption efficiency. The coordination number ratio confirmed the adsorption mechanisms: basalt and argillite exhibited inner-sphere (IS) complexation, granite showed a transition from ion exchange to IS complexation due to pH effects, and mudrock exhibited IS complexation after Cs+ dehydration. A novel EXAFS fitting strategy is proposed to deliver reasonable fitting parameters. Moreover, a 2D wavelet transform with XANES could deliver another viewpoint of the adsorption mechanisms. Based on the comparison with adsorption parameters of the standard CsNO3 sample, an iterative check algorithm is proposed then to yield the reasonable outcomes. The preliminary results found that the hydration layer adsorption mechanism of argillite and mudrock are similar to CsNO3, while granite-W and mudrock displayed similar structural information for outer-sphere (OS) complexes, indicating IS complexation caused by Cs+ dehydration.